Single Grazing Is More Detrimental to Grasslands Than Mixed Grazing: Evidence From the Response of Functional Traits of Dominant Plants to Grazing Systems - Wang, Zheng; Zhang, Jinghui; Li, Zhiyong; Liu, Huamin; Wang, Lixin; Wang, Wen; Wang, Yang; Liang, Cunzhu (Frontiers in Ecology and Evolution, 2021)
Plant functional traits reflect species ecological strategies and determine how plants respond to environmental changes, however, how dominant species in the Inner Mongolia grassland adapt to different grazing systems by changing their functional traits has not been systematically investigated. In this study, we established four 7-year grazing treatments in the Inner Mongolia grassland: cattle grazing, sheep grazing, mixed sheep and cattle grazing, and no grazing. Fourteen functional traits of 3 dominant species (Stipa grandis, Leymus chinensis and Cleistogenes squarrosa) were measured under the different grazing treatments. We found convergences of plant functional traits that indicate herbivory avoidance or tolerance. Plants reduced their vegetative height (VH) and stem : leaf ratio (SLR) to avoid grazing; increased their ability to acquire resources by increasing their specific leaf area (SLA), leaf nitrogen concentration (LNC), and leaf phosphorus concentration (LPC); and reduced their leaf dry matter content (LDMC) to tolerate grazing. Moreover, plants may adapt to grazing by increasing the intraspecific variability of their functional traits. Sheep-only grazing adversely affected L. chinensis growth and survival, while cattle-only grazing hindered S. grandis growth and increased the intraspecific variability of its plant functional traits. Our study emphasizes that intraspecific variability is an important indicator of the responses of plant functional traits to grazing. Since single grazing is more detrimental to the functional traits of dominant plants, we suggest that mixed cattle and sheep grazing may be a more environmentally friendly and sustainable practice for the Inner Mongolia grassland than single grazing.